Regularities of solid-phase reduction of iron oxides under conditions of combined chemical-catalytic and energetic influence - Grishin , O.M.; Proidak , Yu.S. (Theory and Practice of Metallurgy, 2025)
Purpose. The purpose of the work is a physicochemical analysis of the intensification of the process of solid-phase iron reduction under the conditions of the joint influence of catalytic additives and an electromagnetic field (EMF). Methodology. The experiments were conducted in an alternating magnetic field with a frequency from industrial to ultrasonic using the thermogravimetric method. The process of reduction of various iron ore materials was studied in the temperature range of 873-1373 К Results. The results of laboratory experiments indicate the influence of the electromagnetic field and intensifying catalytic additives on the process of solid-phase reduction of various iron ore materials. The non-additivity of the results of the joint influence of additives and an intensifying EMF is shown. The study of the influence of various process parameters on the rate and degree of reduction of iron ore materials is carried out. Scientific novelty. The joint intensifying effect of catalytic additives and EMF on the process of solid-phase iron reduction is experimentally shown. A physicochemical justification of the non-additivity of the joint influence on the kinetics of the reduction process is proposed. Practical significance. Intensification of the processes of solid-phase reduction of iron ore raw materials provides a significant increase in the productivity of direct iron production technologies - process intensification and process productivity.